The lost [large type] - Robb, J. D., 1950-; Gaffney, Patricia; Blayney, Mary; Langan, Ruth Ryan (Thorndike Press, 2010)
Venture into a world where the rules of love of time and of place can be forever lost ... In J. D. Robb's Missing in Death Eve Dallas investigates a woman's disappearance from a New York City ferry. In The Dog Days of Laurie Summer by Patricia Gaffney a woman awakens after an accident to a world both familiar and unsettling. A cursed man is Lost in Paradise in Mary Blayney's story and a young woman unearths a family secret in Ruth Ryan Langan's Legacy.